Efektifitas Filtrat Kultur yang Dihasilkan Oleh Berbagai Ras Sclerotium Rolfsii Terhadap Pertumbuhan in Vitro Kecambah Kacang Tanah: Effectiveness Of Culture Filtrate Produced By Sclerotium Rolfsii Races Against In Vitro Growth Of Peanut Seedling - A Farid Hemon (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
The objective of this research was to evaluate of culture filtrate effectiveness produced by S. rolfsii races against in vitro growth of peanut seedling. The experiment was inisiated with characterize and hyphal anastomosis group test of S. rolfsii isolates. This experiment has been gotten 4 races (race 1, 8, 6, 9). Four races were proliferated for used as culture filtrate selective agents. This culture filtrate will be used as material to be added with MS medium to peanut seedling growth test. Culture filtrate MS medium (MS+CF) consisted of MS based medium, B5 vitamin, sucrose (30 g/L), agar, and culture filtrate (different concentration 0, 25, 30, 35%). Seeds of peanut (cv. Local Bima, Kelinci, G-250, G-300) were cultivated in different concentration of culture filtrate of MS+CF medium. Results of study showed that culture filtrate from different races affected significantly againts seed germination ability and inhibited growing peanut seedling. Culture filtrate concentration 35% was more inhibited to peanut seedling growing compared with lower culture filtrate concentration or compared control (without culture filtrate).